2019
DOI: 10.1159/000497807
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Decline of Residual Renal Function in the First Year is a Predictor for Early Withdrawal from Peritoneal Dialysis in Non-Diabetic Patients

Abstract: Background/Aims: Little is known about the relationship between residual renal function (RRF) decline in early period and survival in non-diabetic peritoneal dialysis (PD) patients. Methods: A total of 567 non-diabetic patients who began PD from January 1, 2005 to June 30, 2013 was investigated. The rate of RRF decline was determined by the “slope of the trend equation” of serial RRFs. A composite end-point of all-cause mortality and conversion to hemodialysis (HD) was used, survival status was censored on Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Wang et al. [ 24 ] found that RRF decline in the first year of PD was an independent predictor of prognosis during the first 3 years of PD therapy, while after more than 3 years, RRF decline no longer correlated with clinical outcomes. Another notable point is that patients were younger in the dialysis inadequacy group.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. [ 24 ] found that RRF decline in the first year of PD was an independent predictor of prognosis during the first 3 years of PD therapy, while after more than 3 years, RRF decline no longer correlated with clinical outcomes. Another notable point is that patients were younger in the dialysis inadequacy group.…”
Section: Discussionmentioning
confidence: 99%
“…As RRF decreases, PD is usually increased to compensate for inadequate dialysis [11]. Linear regression analysis was used to further understand the impact of cystatin C removal by RRF and PD on serum cystatin C levels.…”
Section: Discussionmentioning
confidence: 99%
“…Only RRF could serve as an independent predictor of prognosis [8,9], and strong RRF was an important guarantee for PD patients to maintain adequate dialysis [10]. The rapid decline of RRF in the first year is an independent risk factor for PD patient death and withdrawal [11]. Thus, the RRF of PD patients should be regularly monitored to characterize factors that contribute to the rapid decline of RRF and take timely intervention measures to protect RRF.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the multivariate Cox proportional hazards model showed that the level of serum albumin was a relevant risk factor for CAPD patients to withdraw from treatment. Chen HL [15] , Griva K [18] , Wang J [19] ,et al found that lower serum albumin levels were associated with an increased risk of technical failure in analysis of risk factors related to PD patients. The results of our analysis showed that the withdrawal risk of patients with serum albumin above 35 g/L was 43.7% lower than that of patients below 35 g/L.…”
Section: Discussionmentioning
confidence: 99%